Understanding the Stability of Salt-Inclusion Phases for Nuclear Waste-forms through Volume-based Thermodynamics. Issue 1 (December 2018) - Moore, Emily; Kocevski, Vancho; Juillerat, Christian; Morrison, Gregory; Zhao, Mingyang; Brinkman, Kyle; Loye, Hans-Conrad; Besmann, Theodore
Abstract Formation enthalpies and Gibbs energies of actinide and rare-earth containing SIMs with silicate and germanate frameworks are reported. Volume-based thermodynamics (VBT) techniques complemented by density functional theory (DFT) were adapted and applied to these complex structures. VBT and DFT results were in closest agreement for the smaller framework silicate structure, whereas DFT in general predicts less negative enthalpies across all SIMs, regardless of framework type. Both methods predict the rare-earth silicates to be the most stable of the comparable structures calculated, with VBT results being in good agreement with the limited experimental values available from drop solution calorimetry.